2000
DOI: 10.1002/1520-6300(200007/08)12:4<503::aid-ajhb10>3.0.co;2-h
|View full text |Cite
|
Sign up to set email alerts
|

Changes in menarcheal age in girls exposed to war conditions

Abstract: The purpose of this study was to assess changes in mean menarcheal age of girls in the city of Sibenik in the period from mid-1980s to the mid-1990s. Sibenik is a Dalmatian town which was exposed to hard war conditions in 1991-1995. Menarcheal status of Sibenik girls was surveyed three times, in 1981, 1985, and 1996, and included 720, 1,207, and 1,680 girls, respectively, ages 9.5-16.5 years. Mean menarcheal age was estimated by the status quo method and application of probit analysis. Results show a slight de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(30 citation statements)
references
References 10 publications
2
26
0
Order By: Relevance
“…In line with this reasoning, Hungarian girls with dead fathers married at later ages than girls with fathers present (although the eventual number of children was similar [19]). The generality of these findings is not known because studies focusing explicitly on the effects of father's death on daughters' maturation and/or reproduction are extremely scarce [12,20] and only two of them [13,19] were performed in developed countries. However, outcomes of such studies, including the current one, contrast with the findings of studies where the father's absence occurs owing to divorce/abandonment, which often enhances maturation and/or reproduction [1,4,5,12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In line with this reasoning, Hungarian girls with dead fathers married at later ages than girls with fathers present (although the eventual number of children was similar [19]). The generality of these findings is not known because studies focusing explicitly on the effects of father's death on daughters' maturation and/or reproduction are extremely scarce [12,20] and only two of them [13,19] were performed in developed countries. However, outcomes of such studies, including the current one, contrast with the findings of studies where the father's absence occurs owing to divorce/abandonment, which often enhances maturation and/or reproduction [1,4,5,12].…”
Section: Discussionmentioning
confidence: 99%
“…Such studies would be particularly informative in situations such as natural disasters and warfare, where causes of death appear random with respect to possible dispositions to any particular life-history strategy. Indeed, contrary to the findings of the majority of studies of the father's absence, stress owing to war conditions, including poverty as well as psychological and physical trauma, appeared to delay, rather than speed up the onset of menarche [13].…”
Section: Introductionmentioning
confidence: 99%
“…Children and adolescents who reached more advanced stages of sexual maturity (3rd, 4th or 5th) before early 1980s, did not respond as dramatically to social changes taking place during this period. A number of authors have confirmed that moderate stress enhances the rate of sexual maturation (Campbell and Udry, 1995;Chilsholm et al, 2005;Surbey, 1990;Wierson et al, 1993), whereas extreme stress has the opposite effect (Dubrova et al, 1995;Prebeg and Bralic, 2000). The mean age of the appearance of full sexual maturation (fifth stage) was extremely delayed in 1980.…”
Section: Discussionmentioning
confidence: 99%
“…Stress due to war conditions, including poverty as well as psychological and physical trauma, appeared to delay, rather than speed onset of menarche. Girls exposed to war conditions experienced a reversal in the secular trend of menarcheal timing (Preberg & Bralic, 2000;Tahirovic, 1998). In sum, environmental stress is related to menarcheal timing in a complex manner; severe physical and psychological stressors such as war conditions or extreme malnutrition delay menarche whereas stressful family environments (i.e., father absence or mother's mental illness) may trigger early menarche.…”
Section: The Etiology Of Early Puberty: Three Hypothesesmentioning
confidence: 99%